Teknik Komunikasi Persuasif: Studi Channel Youtube Munzalan TV Official "Allah Ajarkan Jalan Rezeki Berlipat Ganda!" - Ayu (Ad-DA'WAH, 2025)
This study aims to analyze the persuasive communication techniques used by Ustadz Luqmanul Hakim in a lecture on the Munzalan TV Official YouTube Channel entitled "Allah Teaches the Way to Double Your Provisions!" The study uses a qualitative content analysis method with a descriptive approach. Data were obtained through lecture video transcripts which were then analyzed based on Aristotle's rhetorical theory including ethos, pathos, and logos. The results show that Ustadz Luqmanul Hakim combines these three aspects harmoniously: ethos is seen from the credibility and exemplary nature of his preaching, pathos appears through emotional touch and familiar language, while logos is seen from logical arguments sourced from the Qur'an and hadith. The application of this persuasive technique makes the preaching message not only informative, but also inspiring and encourages changes in audience behavior